Contemporary Diagnosis and Management of Patients With Myocardial Infarction in the Absence of Obstructive Coronary Artery Disease: A Scientific Statement From the American Heart Association. Issue 18 (30th April 2019) - Tamis-Holland, Jacqueline E.; Jneid, Hani; Reynolds, Harmony R.; Agewall, Stefan; Brilakis, Emmanouil S.; Brown, Todd M.; Lerman, Amir; Cushman, Mary; Kumbhani, Dharam J.; Arslanian-Engoren, Cynthia; Bolger, Ann F.; Beltrame, John F.
Abstract : Myocardial infarction in the absence of obstructive coronary artery disease is found in ≈5% to 6% of all patients with acute infarction who are referred for coronary angiography. There are a variety of causes that can result in this clinical condition. As such, it is important that patients are appropriately diagnosed and an evaluation to uncover the correct cause is performed so that, when possible, specific therapies to treat the underlying cause can be prescribed. This statement provides a formal and updated definition for the broadly labelled term MINOCA (incorporating the definition of acute myocardial infarction from the newly released "Fourth Universal Definition of Myocardial Infarction") and provides a clinically useful framework and algorithms for the diagnostic evaluation and management of patients with myocardial infarction in the absence of obstructive coronary artery disease.